Transforming female labour force through micro enterprises: a proposed coceptual framework - Mohd Safwan Ghazali; Muhammad Adidinizar Zia Ahmad Kusairee; Peck Leong Tan (Faculty of Entrepreneurship and Business,UMK, 2015)
This paper will determine the factors that influence female labour force participation rate (LFPR) in Malaysia. Simultaneously, this paper will establish whether female LFPR can be encouraged to participate into micro enterprises. Female participation in labour force is reflected by changes in economic activity, educational attainment, fertility rates, social norms, and other factors. The paper will discern the controlling factors that stimulate female LFPR and how these factors can be further synergize through micro enterprises. Other factors which affect the decision making process such as education, marital status, child care, elderly care, age, parent’s education level and parent’s occupational level are also analysed and discussed in the context of factors that influence decision to work among women in Malaysia.